2021
DOI: 10.1016/j.esmoop.2021.100146
|View full text |Cite
|
Sign up to set email alerts
|

Impact of the 12-gene recurrence score assay on deciding adjuvant chemotherapy for stage II and IIIA/B colon cancer: the SUNRISE-DI study

Abstract: Background: Recent advances in adjuvant chemotherapy for early colon cancer have widened physicians' recommendations on the regimen and duration (3 or 6 months) of the treatment. We conducted this prospective study to evaluate whether the 12-gene recurrence score (12-RS) assay affected physicians' recommendations on adjuvant treatment selection. Patients and methods: Patients with stage IIIA/IIIB or stage II colon cancer were enrolled. After the patients discussed adjuvant treatment with their treating physici… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

0
6
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(6 citation statements)
references
References 26 publications
(35 reference statements)
0
6
0
Order By: Relevance
“…Multiple genomic assays have been developed to identify high-risk subgroups in the heterogeneous population of stage II colorectal cancer patients that might benefit from adjuvant chemotherapy (5)(6)(7)(8)(9)(10). Currently, four genomic tests (the 12-gene assay, an 18-gene expression assay, a 482gene signature, and the Immunoscore assay) are available for clinical use in the US.…”
Section: Discussionmentioning
confidence: 99%
“…Multiple genomic assays have been developed to identify high-risk subgroups in the heterogeneous population of stage II colorectal cancer patients that might benefit from adjuvant chemotherapy (5)(6)(7)(8)(9)(10). Currently, four genomic tests (the 12-gene assay, an 18-gene expression assay, a 482gene signature, and the Immunoscore assay) are available for clinical use in the US.…”
Section: Discussionmentioning
confidence: 99%
“…In each strategy, the patients were offered either the 12gene assay or the 18-gene expression assay, or the 482-gene signature or the Immunoscore assay and then distributed into two risk categories, either high risk or low risk. This stratification of patients into the two risk categories of high and low was based on the recurrence score of the marketed genomic tests (5)(6)(7)(8)(9)(10). Furthermore, the patients in the high-risk categories of the four genomic tests were assumed to be administered adjuvant chemotherapy, while the patients in the low-risk categories of the four genomic tests were assumed to be treated without adjuvant chemotherapy.…”
Section: Overview Of the Modelmentioning
confidence: 99%
“…More recently, with advances in genomic medicine, precision molecular diagnostic tests have offered possibilities to predict disease relapse and guide adjuvant therapy decisions (5)(6)(7)(8)(9)(10). Currently, there are four tests being marketed for clinical use in the United States (US): a 12-gene assay; an 18-gene expression assay, a 482-gene signature, and the Immunoscore assay.…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…12-Gene recurrence score assay is a test that evaluates the risk of recurrence of colon cancer using seven genes and ve reference genes and is used in medical practice in the United States and some European countries [1][2][3]. Attempts to evaluate this assay in Asia have also demonstrated that the 12-Gene recurrence score assay is a prognostic factor independent of pathologic stage classi cation and can change the actual chemotherapy prescription status after surgery [4,5]. Other assays that classify colon cancer into several subtypes based on RNA expression have shown that the mesenchymal subtype responds less effectively to adjuvant therapy, including oxaliplatin, whereas the microsatellite instability subtype responds more effectively [6].…”
Section: Introductionmentioning
confidence: 99%